Preparation of solid-waste-based magnetic hierarchical porous material and method for removing micro / nano plastic in polluted water by using solid-waste-based magnetic hierarchical porous material

By preparing solid waste-based magnetic multi-stage porous materials, using their magnetic and multi-stage porous structures to adsorb and separate micro/nanoplastics in contaminated water bodies, the problem of difficulty in removing micro/nanoplastics in the prior art is solved, and high efficiency is achieved , recyclable removal effect.

CN119386819AActive Publication Date: 2025-02-07INST OF SOIL SCI CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411931657.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-07
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove micro/nanoplastics in contaminated water bodies, especially due to the small particle size, wide distribution and difficulty in degradation of micro/nanoplastics, which makes it difficult to remove in water bodies.

Method used

Solid waste-based magnetic multi-stage porous materials are prepared by using biomass raw materials, bauxite waste slag, and coal gangue as raw materials, and through roasting and hydrothermal crystallization, the micro/nanoplastics are adsorbed using their magnetic and multi-stage porous structures. and separate under the action of a magnetic field.

Benefits of technology

It realizes efficient removal of micro/nanoplastics in water, the material has good adsorption effect and magnetic recovery performance, and is recycled through sodium chloride solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386819A_ABST
    Figure CN119386819A_ABST
Patent Text Reader

Abstract

The invention provides preparation of a solid-waste-based magnetic hierarchical porous material and a method for removing micro / nano plastic in a polluted water body by using the solid-waste-based magnetic hierarchical porous material, and belongs to the field of solid waste resource utilization and water treatment. The invention provides a preparation method of a solid-waste-based magnetic hierarchical porous material, which comprises the following steps: mixing a biomass raw material, bauxite waste residue, coal gangue and strong alkali, and roasting in a protective atmosphere to obtain roasted clinker containing biochar and iron; and mixing the roasted clinker with water, and carrying out hydrothermal crystallization reaction to generate a molecular sieve, thereby obtaining the solid-waste-based magnetic hierarchical porous material. The solid-waste-based magnetic hierarchical porous material not only contains macropores of biomass charcoal, but also contains micropores of a molecular sieve, can be used for adsorbing micro / nano plastic in a water body, and can be recycled for multiple times. The solid waste raw material is a large amount of stockpiled solid waste, the effect of treating waste with waste can be achieved by using the solid waste raw material to prepare the material, and obvious economic and environmental benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid waste resource utilization and water treatment, and in particular to a method for preparing a solid waste-based magnetic multi-level porous material and removing micro / nano plastics from polluted water. Background Art

[0002] Microplastics usually refer to plastic particles with a particle size of less than 5mm, and nanoplastics refer to plastic particles with a particle size of less than 1000nm. Micro / nanoplastics can be divided into primary plastics and secondary plastics according to their source. Primary micro / nanoplastics are mostly tiny plastic particles contained in industrial products, which are directly released into the macro-environment during the production and use process. Secondary micro- and nanoplastics are formed after cracking, wear or degradation through physical, chemical and biological effects. Micro / nanoplastics have the characteristics of small particle size, wide distribution and difficulty in degradation, which leads to their strong bioaccumulation and environmental persistence. As the size of plastics decreases, their environmental migration ability and biological toxicity become more obvious, which in turn poses a potential threat to the ecosystem.

[0003] Aquatic ecosystems are considered to be ecosystems that accumulate micro / nano plastics. Surface runoff is the main way for micro / nano plastics to enter aquatic ecosystems. At the same time, there are often different types of micro / nano plastics in aquatic ecosystems, such as fragments, fibers, particles, foam, etc., and their morphology and size vary greatly depending on the type of plastic and the way it is broken. Therefore, the distribution concentration of micro / nano plastics in water bodies is high, and there are many types of morphology and size, making it difficult to manage.

[0004] The removal methods of micro / nano plastics can be mainly divided into five categories: filtration, coagulation, biological method, adsorption and advanced oxidation. Among them, filtration and advanced oxidation methods are limited by the pore size of plastics, have problems such as low efficiency, and the actual application effect is poor. The more widely studied adsorption method is difficult to apply to actual water bodies because materials such as biochar have good adsorption effects but cannot be recycled and reused. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a solid waste-based magnetic multi-level porous material and removing micro / nano plastics from polluted water. The solid waste-based magnetic multi-level porous material is prepared by using biomass raw materials, bauxite waste slag, and coal gangue as raw materials, and undergoing steps such as roasting and crystallization, which can efficiently remove micro and / or nano plastics from water.

[0006] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a solid waste-based magnetic multi-level porous material, comprising the following steps: The biomass raw materials, bauxite waste slag, coal gangue and strong alkali are mixed and roasted under a protective atmosphere to obtain roasted clinker containing biochar and iron; The roasted clinker is mixed with water and subjected to a hydrothermal crystallization reaction to generate a molecular sieve, thereby obtaining the solid waste-based magnetic multi-level porous material.

[0007] Preferably, the bauxite waste slag comprises, by mass fraction, 30-35% Fe2O3, 15-20% SiO2, 25-30% Al2O3, 2-10% CaO, 5-10% Na2O, 2-10% TiO2 and 1.5-2% impurities.

[0008] Preferably, in terms of mass fraction, the coal gangue includes Fe2O3 0.5-1%, SiO2 55-60%, Al2O3 40-45%, CaO 0.15-0.2%, TiO2 1.02% and impurities 0.5-1%.

[0009] Preferably, the molar ratio of the total carbon element to the aluminum element in the biomass raw material, bauxite waste slag, and coal gangue is 0.2-0.4:1; The total molar ratio of aluminum element to silicon element is 1:0.8~1.2.

[0010] Preferably, the molar ratio of the total aluminum element in the biomass raw material, bauxite waste slag, and coal gangue to the metal element in the strong base is 1:1.5-5.

[0011] Preferably, the calcination temperature is 400-800° C. and the calcination time is 1-3 hours.

[0012] Preferably, the temperature of the hydrothermal crystallization reaction is 90-150° C., and the time is 3-24 hours.

[0013] The present invention also provides a solid waste-based magnetic multilevel porous material prepared by the preparation method described in the above technical solution.

[0014] The present invention also provides a method for removing micro- and / or nano-plastics from polluted water, comprising the following steps: (1) The solid waste-based magnetic multilevel porous material described in the above technical solution is mixed with polluted water to adsorb micro- and / or nano-plastics, and then separated under the action of a magnetic field to obtain a solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics.

[0015] Preferably, the method further comprises: (2) mixing the solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics with a desorbent to desorb the micro- and / or nano-plastics to obtain the desorbed solid waste-based magnetic multilevel porous material; (3) Repeat steps (1) to (2) on the desorbed solid waste-based magnetic multi-level porous material.

[0016] The solid waste raw materials (biomass raw materials, bauxite waste, coal gangue) used in the present invention are large-scale solid wastes that are stored, with low utilization rates and great environmental hazards. The materials prepared from them can play the role of treating waste with waste, and the magnetic biomass charcoal-molecular sieve composite material is prepared, which contains both the macropores of biomass charcoal and the micropores of molecular sieves. When used as an adsorption material, it can deal with micro / nano plastics of various sizes. At the same time, the material is magnetic and can be recycled under the condition of an external magnetic field, providing technical support for removing micro / nano plastics from water bodies.

[0017] After adsorption is completed, the multi-level porous material can be regenerated by sodium chloride solution to achieve recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD spectrum of the solid waste-based magnetic multi-level porous material in Example 1; Figure 2 This is the SEM spectrum of the solid waste-based magnetic multi-level porous material in Example 1; Figure 3 The removal effect of the solid waste-based magnetic multi-level porous material on PE plastic balls in water bodies in Example 1; Figure 4 This is the removal effect of the solid waste-based magnetic multi-level porous material on PS plastic balls in water after five cycles in Example 3. DETAILED DESCRIPTION

[0019] The present invention provides a method for preparing a solid waste-based magnetic multi-level porous material, comprising the following steps: The biomass raw materials, bauxite waste slag, coal gangue and strong alkali are mixed and roasted under a protective atmosphere to obtain roasted clinker containing biochar and iron; The roasted clinker is mixed with water and subjected to a hydrothermal crystallization reaction to generate a molecular sieve, thereby obtaining the solid waste-based magnetic multi-level porous material.

[0020] The invention mixes biomass raw materials, bauxite waste slag, coal gangue and strong alkali, and then roasts them under a protective atmosphere to obtain roasted clinker containing biochar and iron.

[0021] In the present invention, the mixing preferably includes: grinding the biomass raw material, bauxite waste slag and coal gangue through a 100-mesh sieve respectively, mixing and drying, and then mixing with a strong base.

[0022] In the present invention, the molar ratio of the total carbon element to the aluminum element in the biomass raw materials, bauxite slag and coal gangue is preferably 0.2~0.4:1, and the molar ratio of the total aluminum element to the silicon element is 1:1; in a specific embodiment of the present invention, the molar ratio of the total carbon element to the aluminum element in the biomass raw materials, bauxite slag and coal gangue can be 0.2:1, 0.3:1 or 0.4:1, and the molar ratio of the total aluminum element to the silicon element is preferably 1:0.8~1.2. In a specific embodiment of the present invention, the molar ratio of the total aluminum element to the silicon element can be 1:0.8, 1:0.9, 1:1, 1.1: or 1.2:.

[0023] In the present invention, the biomass raw material preferably includes corn stalks.

[0024] In the present invention, the bauxite waste slag preferably comprises Bayer process red mud; and the molar ratio of aluminum to silicon in the bauxite waste slag is preferably greater than 1.

[0025] In terms of mass fraction, the bauxite waste slag preferably includes 30-35% of Fe2O3. In a specific embodiment of the present invention, the mass fraction of Fe2O3 in the bauxite waste slag may be 30%, 31%, 32%, 33%, 33.8%, 34% or 35%; In terms of mass fraction, the bauxite waste slag preferably includes SiO215-20%. In a specific embodiment of the present invention, the mass fraction of SiO2 in the bauxite waste slag may be 15%, 16%, 16.06%, 17%, 18%, 19% or 20%; In terms of mass fraction, the bauxite waste slag preferably includes Al2O3 25-30%. In a specific embodiment of the present invention, the mass fraction of Al2O3 in the bauxite waste slag may be 25%, 26%, 26%, 27%, 28%, 29.04% or 30%; In terms of mass fraction, the bauxite waste slag preferably includes 2-10% CaO. In a specific embodiment of the present invention, the mass fraction of CaO in the bauxite waste slag may be 2%, 3%, 4%, 5%, 6%, 6.67%, 7%, 8%, 9% or 10%; In terms of mass fraction, the bauxite waste slag preferably includes 5-10% Na2O. In a specific embodiment of the present invention, the mass fraction of Na2O in the bauxite waste slag may be 5%, 6%, 6.58%, 7%, 8%, 9% or 10%; In terms of mass fraction, the bauxite waste slag preferably includes TiO22-10%. In a specific embodiment of the present invention, the mass fraction of TiO2 in the bauxite waste slag may be 2%, 3%, 4%, 5%, 5.86%, 6%, 7%, 8%, 9% or 10%; In terms of mass fraction, the bauxite waste slag preferably includes 1.5-2% impurities. In a specific embodiment of the present invention, the mass fraction of the impurities in the bauxite waste slag may be 1.5%, 1.6%, 1.63%, 1.7%, 1.8%, 1.9% or 2%.

[0026] In the present invention, the molar ratio of aluminum to silicon in the coal gangue is preferably less than 1.

[0027] In terms of mass fraction, the coal gangue preferably includes Fe2O3 0.5-1%. In a specific embodiment of the present invention, the mass fraction of Fe2O3 in the coal gangue may be 0.5%, 0.6%, 0.62%, 0.7%, 0.8%, 0.9% or 1%; In terms of mass fraction, the coal gangue preferably includes SiO255-60%. In a specific embodiment of the present invention, the mass fraction of SiO2 in the coal gangue may be 55%, 55.48%, 56%, 57%, 58%, 59% or 60%; In terms of mass fraction, the coal gangue preferably includes 40-45% Al2O3. In a specific embodiment of the present invention, the mass fraction of Al2O3 in the coal gangue may be 45%, 41%, 41.83%, 42%, 43%, 44% or 45%; In terms of mass fraction, the coal gangue preferably includes 0.15-0.2% CaO. In a specific embodiment of the present invention, the mass fraction of CaO in the coal gangue may be 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.2%; In terms of mass fraction, the coal gangue preferably includes TiO21.02%; In terms of mass fraction, the coal gangue preferably includes 0.5-1% impurities. In a specific embodiment of the present invention, the mass fraction of the impurities in the coal gangue can be 0.5%, 0.6%, 0.7%, 0.8%, 0.87%, 0.9% or 1%.

[0028] In the present invention, the molar ratio of the total aluminum element in the biomass raw materials, bauxite slag and coal gangue to the metal element in the strong base is preferably 1:2-6. In a specific embodiment of the present invention, the molar ratio of the total aluminum element in the biomass raw materials, bauxite slag and coal gangue to the metal element in the strong base can be 1:2, 1:3, 1:4, 1:5 or 1:6; the strong base preferably includes sodium hydroxide.

[0029] In the present invention, the calcination temperature is preferably 400-800°C, and the time is 1-3h; in a specific embodiment of the present invention, the calcination temperature can be 400°C, 500°C, 600°C, 700°C or 800°C, and the time can be 1h, 2h or 3h.

[0030] In the present invention, the calcination is preferably carried out in a tubular furnace in a nitrogen atmosphere; the flow rate of the nitrogen is preferably 200 mL / min.

[0031] During the roasting process, the biomass raw materials are carbonized, the alumina phase is activated, and the iron phase in the bauxite is reduced.

[0032] After obtaining the roasted clinker containing biochar and iron, the present invention mixes the roasted clinker with water and performs a hydrothermal crystallization reaction to generate a molecular sieve, thereby obtaining the solid waste-based magnetic multi-level porous material.

[0033] In the present invention, the mass ratio of the roasted clinker to water is preferably 1:10-15. In a specific embodiment of the present invention, the mass ratio of the roasted clinker to water can be 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0034] In the present invention, the temperature of the hydrothermal crystallization reaction is preferably 90-150°C, and the time is preferably 3-24h. In a specific embodiment of the present invention, the temperature of the hydrothermal crystallization reaction can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, and the time can be 3h, 5h, 8h, 12h, 15h, 18h, 21h or 24h.

[0035] After the hydrothermal crystallization reaction is completed, the present invention preferably filters the obtained product, and then washes and dries the filtered solid.

[0036] The present invention also provides a solid waste-based magnetic multi-level porous material prepared by the preparation method described in the above technical solution The present invention also provides a method for removing micro- and / or nano-plastics from polluted water, comprising the following steps: (1) The solid waste-based magnetic multilevel porous material described in the above technical solution is mixed with polluted water to adsorb micro- and / or nano-plastics, and then separated under the action of a magnetic field to obtain a solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics.

[0037] In the present invention, the concentration of the solid waste-based magnetic multilevel porous material in the mixed solution is preferably 50 mg / L.

[0038] In the present invention, the adsorption time is preferably 1 to 4 hours.

[0039] In the present invention, the strength of the magnetic field is preferably 20-100 kA / m. In a specific embodiment of the present invention, the strength of the magnetic field can be 20 kA / m, 30 kA / m, 40 kA / m, 50 kA / m, 60 kA / m, 70 kA / m, 80 kA / m, 90 kA / m or 100 kA / m.

[0040] In the present invention, the method preferably further comprises: (2) mixing the solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics with a desorbent to desorb the micro- and / or nano-plastics, thereby obtaining the desorbed solid waste-based magnetic multilevel porous material; In the present invention, the desorbent is preferably a sodium chloride solution, and the concentration of the sodium chloride solution is preferably 1-3 mol / L.

[0041] In the present invention, the desorption temperature is preferably 15-35° C., and the desorption time is preferably 0.5-3 h.

[0042] (3) Repeat steps (1) to (2) on the desorbed solid waste-based magnetic multi-level porous material.

[0043] The preparation of the solid waste-based magnetic multi-level porous material provided by the present invention and the method for removing micro / nano plastics from polluted water bodies are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1 The biomass raw materials (corn stalks), bauxite waste residue (by mass fraction, the composition is Fe2O333.96%, SiO216.06%, Al2O329.24%, CaO 6.67%, Na2O 6.58%, TiO25.86%, others 1.63%), and coal gangue (by mass fraction, the composition is Fe2O30.62%, SiO255.48%, Al2O341.83%, CaO 0.18%, TiO21.02%, others 0.87%) were ground through a 100 mesh sieve and mixed according to n (C): n (Al): n (Si) = 0.2:1:1. The dried mixed raw materials were mixed with sodium hydroxide at a ratio of n (Na): n (Al) = 3 and placed in a tubular furnace in a nitrogen atmosphere for roasting. The roasting temperature was selected to be 600 ° C and the roasting time was 1.6 hours to obtain roasted clinker.

[0045] 2 g of the calcined clinker was added to a 50 mL polytetrafluoroethylene liner reactor, 30 mL of water was added, and the mixture was hydroheated at 100° C. for 12 h. After solid-liquid separation, the obtained solid was washed and dried to obtain a solid waste-based magnetic multilevel porous material.

[0046] The solid waste-based magnetic multilevel porous material of Example 1 was placed in a fluorescently labeled PE plastic ball solution with a particle size of 50 nm and a concentration of 10 mg / L. The concentration of the solid waste-based magnetic multilevel porous material was 50 mg / L. After an adsorption time of 2 hours, the solid waste-based magnetic multilevel porous material was separated from the solution by a magnet, and the removal rate of PE plastic balls in the solution reached 96.7%.

[0047] Figure 1 This is the XRD spectrum of the solid waste-based magnetic multi-level porous material in Example 1; Depend on Figure 1 It can be seen that the synthesized material contains type A zeolite and magnetite. Type A zeolite has micropores and has a good adsorption effect on small-sized nanoplastics. Magnetite has superparamagnetism and can be recovered under the condition of an external magnetic field.

[0048] Figure 2 This is the SEM spectrum of the solid waste-based magnetic multi-level porous material in Example 1; Depend on Figure 2 It can be seen that a composite material including biochar, zeolite and magnetite was synthesized, and the zeolite phase, magnetic phase and biochar were uniformly dispersed.

[0049] Figure 3 This is the removal effect of the solid waste-based magnetic multi-level porous material in Example 1 on PE plastic balls in water.

[0050] Example 2 The biomass raw materials (corn stalks), bauxite waste residue (by mass fraction, the composition is Fe2O333.96%, SiO216.06%, Al2O329.24%, CaO 6.67%, Na2O 6.58%, TiO25.86%, other 1.63%), and coal gangue (by mass fraction, the composition is Fe2O30.62%, SiO255.48%, Al2O341.83%, CaO 0.18%, TiO21.02%, other 0.87%) were ground through a 100 mesh sieve and mixed according to n (C): n (Al): n (Si) = 0.3:1:1. The dried mixed raw materials were mixed with sodium hydroxide at a ratio of n (Na): n (Al) = 4 and placed in a tubular furnace in a nitrogen atmosphere for roasting. The roasting temperature was selected to be 700 ° C and the roasting time was 2.2 h to obtain roasted clinker.

[0051] 3 g of the roasted clinker was added to a 50 mL polytetrafluoroethylene liner reactor, 30 mL of water was added, and the mixture was hydroheated at 100° C. for 16 h. After solid-liquid separation, the obtained solid was washed and dried to obtain a solid waste-based magnetic multilevel porous material.

[0052] The solid waste-based magnetic multilevel porous material of Example 2 was placed in a fluorescently labeled PVC plastic ball solution with a particle size of 1 μm and a concentration of 10 mg / L. The concentration of the solid waste-based magnetic multilevel porous material was 50 mg / L, and the adsorption time was 3 hours. The solid waste-based magnetic multilevel porous material was then separated from the solution by a magnet, and the removal rate of the PVC plastic balls in the solution reached 94.8%.

[0053] The adsorbed solid waste-based magnetic multilevel porous material was regenerated by 1.5 mol / L sodium chloride solution at 25°C for 1.5 h, and then added to a 10 mg / L fluorescent labeled PVC plastic ball solution (the concentration of the solid waste-based magnetic multilevel porous material was 50 mg / L) for adsorption for 3 h, with a removal rate of 91.8%.

[0054] Example 3 The biomass raw materials (green tea scraps), bauxite waste residue (by mass fraction, the composition is Fe2O333.96%, SiO216.06%, Al2O329.24%, CaO 6.67%, Na2O 6.58%, TiO25.86%, others 1.63%), and coal gangue (by mass fraction, the composition is Fe2O30.62%, SiO255.48%, Al2O341.83%, CaO 0.18%, TiO21.02%, others 0.87%) were ground through a 100 mesh sieve and mixed according to n (C): n (Al): n (Si) = 0.25:1:1. The dried mixed raw materials were mixed with sodium hydroxide at a ratio of n (Na): n (Al) = 3.3 and placed in a tubular furnace in a nitrogen atmosphere for roasting. The roasting temperature was selected to be 650 ° C and the roasting time was 1.5h to obtain roasted clinker.

[0055] Take 2 g of the roasted clinker and add it into a 50 mL polytetrafluoroethylene lining reactor, add 30 mL of water, and hydroheat at 95°C for 22 h. After solid-liquid separation, the obtained solid is washed and dried to obtain a solid waste-based magnetic multilevel porous material.

[0056] The solid waste-based magnetic multilevel porous material of Example 3 was placed on a fluorescent label surface with a particle size of 1 μm and a concentration of 10 mg / L and NH 4+ In the PS plastic ball solution of the group, the concentration of the solid waste-based magnetic multilevel porous material was 10 mg / L, and the adsorption time was 2 hours. The solid waste-based magnetic multilevel porous material was then separated from the solution by a magnet, and the removal rate of the PS plastic balls in the solution reached 98.3%.

[0057] The adsorbed solid waste-based magnetic multilevel porous material was regenerated by 1.3 mol / L sodium chloride solution at 25°C for 1.5 h, and then added to a 10 mg / L fluorescent labeled PVC plastic ball solution (the concentration of the solid waste-based magnetic multilevel porous material was 10 mg / L) for adsorption for 2 h. The above steps were repeated 5 times, and the removal rates were 93.1%, 91.6%, 91.2%, 90.8% and 90.6%, respectively.

[0058] Figure 4 This is the removal effect of the solid waste-based magnetic multi-level porous material on PS plastic balls in water after five cycles in Example 3.

[0059] Comparative Example 1 RMBC-2 in Example 2 of patent CN 115869909 A.

[0060] Compare with the adsorption experiment of micro / nano plastics by the product in Example 2 of the present invention: The two materials were placed in a fluorescently labeled PVC plastic ball solution with a particle size of 1 μm and a concentration of 10 mg / L, the solid waste-based magnetic multilevel porous material concentration was 50 mg / L, and the adsorption time was 2 hours. The solid waste-based magnetic multilevel porous material was then separated from the solution by a magnet. The removal efficiency of Example 2 of the present invention was 90.9%, and the removal rate of RMBC-2 was 44%.

[0061] In addition, compared with patent CN 115869909 A, the raw materials of the embodiments of the present invention are all solid wastes, no external aluminum silicon source is required, and no suspension liquid is required to synthesize zeolite during operation, which makes the operation simpler.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a solid waste-based magnetic multi-level porous material, characterized in that: The following steps are involved: The biomass raw materials, bauxite waste slag, coal gangue and strong alkali are mixed and roasted under a protective atmosphere to obtain roasted clinker containing biochar and iron; The roasted clinker is mixed with water and subjected to a hydrothermal crystallization reaction to generate a molecular sieve, thereby obtaining the solid waste-based magnetic multi-level porous material.

2. The preparation method according to claim 1, characterized in that: Calculated by mass fraction, the bauxite waste slag includes 30-35% Fe2O3, 15-20% SiO2, 25-30% Al2O3, 2-10% CaO, 5-10% Na2O, 2-10% TiO2 and 1.5-2% impurities.

3. The preparation method according to claim 1, characterized in that: Calculated by mass fraction, the coal gangue includes Fe2O3 0.5-1%, SiO2 55-60%, Al2O3 40-45%, CaO 0.15-0.2%, TiO2 1.02% and impurities 0.5-1%.

4. The preparation method according to any one of claims 1 to 3, characterized in that The molar ratio of the total carbon element to the aluminum element in the biomass raw material, bauxite waste slag and coal gangue is 0.2-0.4:1; The total molar ratio of aluminum element to silicon element is 1:0.8~1.

2.

5. The preparation method according to any one of claims 1 to 3, characterized in that The molar ratio of the total aluminum element in the biomass raw material, bauxite waste slag and coal gangue to the metal element in the strong alkali is 1:2-6.

6. The preparation method according to claim 1, characterized in that: The calcination temperature is 400-800° C. and the calcination time is 1-3 hours.

7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal crystallization reaction is 90-150° C. and the time is 3-24 hours.

8. The solid waste-based magnetic multilevel porous material prepared by the preparation method according to any one of claims 1 to 7.

9. A method for removing micro- and / or nano-plastics from polluted water, characterized in that: The following steps are involved: (1) The solid waste-based magnetic multilevel porous material according to claim 8 is mixed with polluted water to adsorb micro- and / or nano-plastics, and then separated under the action of a magnetic field to obtain a solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics.

10. The method according to claim 9, characterized in that Also includes: (2) mixing the solid waste-based magnetic multilevel porous material adsorbed with micro- and / or nano-plastics with a desorbent to desorb the micro- and / or nano-plastics, thereby obtaining a desorbed solid waste-based magnetic multilevel porous material; (3) Repeat steps (1) to (2) on the desorbed solid waste-based magnetic multi-level porous material.

Citation Information

Patent Citations

  • High-mesoporous-rate lignin hierarchical pore carbon material and preparation method and application thereof

    CN112794324A

  • Biomass-based functional carbon, preparation method thereof and application of biomass-based functional carbon in removal of micro-plastics in water

    CN113070036A

  • Method for preparing magnetic zeolite by utilizing red mud and carbon-containing aluminum-silicon waste

    CN114180588A

  • Method for preparing magnetic porous charcoal-coated molecular sieve through red mud modification

    CN115869909A